Réinvention et détournement du féminin ou Schéhérazade au masculin dans ZABOR ou les psaumes de Kamel Daoud - Souad Atoui-Labidi (Caietele Echinox, 2022)
Scheherazade, an important female character in the collection of tales The Thousand and One Nights, its main storyteller and guarantor since she ensured its continuity by inventing each night a new story to achieve a specific goal: (to) save from the execution. She is also presented as the perfect embodiment of the therapist who wields speech with great intelligence to heal the king of his complexes and his insatiable desire for revenge. But what fate was reserved for her after the thousand and one nights stories? In this article, we analyze the novel by Algerian author Kamel Daoud ZABOR ou les psaumes focusing our attention on the reinvention and diversion of the female character of Scheherazade to the masculine.